Infinite summation formulas related to Riemann Zeta function from hypergeometric series - Chen, Yuwu; Wang, Xiaoxia (Journal of difference equations and applications, 2018)
Applying Gauss and Watson's famous hypergeometric summation theorems, the authors establish two pattern infinite summation formulas involving generalized harmonic numbers related to Riemann Zeta function.